• Jul 2nd 2008, 02:14 PM
tricey36
I am stuck on this problem as I think there is no solution can you please tell me if I am right.

Solve for x:√x-6 - √x-6 = 36

and problem # 2

Solve for x √x-6√x-6 = 15

• Jul 2nd 2008, 02:17 PM
Mathstud28
Quote:

Originally Posted by tricey36
I am stuck on this problem as I think there is no solution can you please tell me if I am right.

Solve for x:√x-6 - √x-6 = 36

and problem # 2

Solve for x √x-6√x-6 = 15

Is this

$\displaystyle \sqrt{x}-6-\sqrt{x}-6=36$?

IF so collecting terms we get

$\displaystyle 0=36+12$

You must have typed thig swrong

For the second one grouping terms we would get
$\displaystyle -5\sqrt{x}=27$

Are you sure this is right?
• Jul 2nd 2008, 02:53 PM
ticbol
Quote:

Originally Posted by Mathstud28
Is this

$\displaystyle \sqrt{x}-6-\sqrt{x}-6=36$?

IF so collecting terms we get

$\displaystyle 0=36+12$

You must have typed thig swrong

For the second one grouping terms we would get
$\displaystyle -5\sqrt{x}=27$

Are you sure this is right?

I think the second is
[sqrt(x-6)]*[sqrt(x-6)] = 15

So,
x -6 = 15

If that is so, then the first could be
sqrt(x-6) -sqrt(x -6) = 36

Which is 0 = 36.

There must be really something wrong.
• Jul 2nd 2008, 03:22 PM
Reckoner
Quote:

Originally Posted by tricey36
I am stuck on this problem as I think there is no solution can you please tell me if I am right.

Solve for x:√x-6 - √x-6 = 36

and problem # 2

Solve for x √x-6√x-6 = 15

As written, these have no solutions (which the others have pointed out):

$\displaystyle \sqrt{x} - 6 - \sqrt x - 6 = 36\Rightarrow 0 = 36$

For the second, assuming you wrote it correctly,

$\displaystyle \sqrt{x} - 6\sqrt x - 6 = 15\Rightarrow -5\sqrt{x} - 6 = 15$

$\displaystyle \Rightarrow\sqrt x = -\frac{21}5$

which has no real solutions.
• Jul 2nd 2008, 05:12 PM
topsquark
Quote:

Originally Posted by tricey36
I am stuck on this problem as I think there is no solution can you please tell me if I am right.

Solve for x:√x-6 - √x-6 = 36

and problem # 2

Solve for x √x-6√x-6 = 15

In the future, PLEASE use parenthesis!

Let me try to read the tea leaves. tricey36, please confirm which of these (if any) you meant.
First problem:
$\displaystyle \sqrt{x} - 6 - \sqrt{x - 6} = 36$
or
$\displaystyle \sqrt{x - 6} - \sqrt{x - 6} = 36$
(Though this one's just silly.)
or
$\displaystyle \sqrt{x - 6} - \sqrt{x} - 6 = 36$

Second problem:
$\displaystyle \sqrt{x - 6} \sqrt{x - 6} = 15$
or
$\displaystyle \sqrt{x} - 6\sqrt{x} - 6 = 15$

These are all I can (reasonably) think of.

-Dan